Answer:
110
Step-by-step explanation:
Answer:
OMGGGGGG IM GONNA KI.LL YOUUUUUUUUUU
Step-by-step explanation:
I need some details... If i can get a little more details with that "check all that apply" and i could get you an answer.
Answer:
Step-by-step explanation:
c. Look for a common factor in each term.
Answer:
Step-by-step explanation:
Hello
A (5;2)
B (-1;-7)
y = ax + b
2 = 5a + b
-7 = -a + b
2 - (-7) = 5a - (-a) + b - b
2 + 7 = 5a + a
9 = 6a
a = 9/6
a = 3/2
2 = 3/2 * 5 + b
b = 2 - 15/2
b = 4/2 - 15/2
b = 11/2
y = 3/2 x + 11/2
y+1= 3/2(x-4)
y + 1 = 3/2 x - 6
y = 3/2 x - 6 - 1
y = 3/2 x - 7 => no
y-4= 3/2(x+1)
y - 4 = 3/2 x + 3/2
y = 3/2 x + 3/2 + 4
y = 3/2 x + 3/2 + 8/2
y = 3/2 x + 11/2 => yes
y+4= 3/2(x-1)
y + 4 = 3/2 x - 3/2
y = 3/2 x - 3/2 - 4
y = 3/2 x - 3/2 - 8/2
y = 3/2 x - 11/2 => no
y-1= 3/2 (x+4)
y - 1 = 3/2 x + 6
y = 3/2 x + 6 + 1
y = 3/2 x + 7 => no